Will they like me? Adolescents' emotional responses to peer evaluation. (March 2014) - Guyer, Amanda E.; Caouette, Justin D.; Lee, Clinton C.; Ruiz, Sarah K.
Relative to children and adults, adolescents are highly focused on being evaluated by peers. This increased attention to peer evaluation has implications for emotion regulation in adolescence, but little is known about the characteristics of the evaluatee and evaluator that influence emotional reactions to evaluative outcomes. The present study used a computer-based social evaluation task to examine predictors of adolescents' emotional responses to feedback from unknown peers. Nine-to-seventeen-year-olds ( N = 36) completed the "chatroom task" and indicated the degree to which each peer would be interested in interacting with them and how good they felt after receiving acceptance and rejection feedback from peers. We examined whether adolescents' age and gender impacted their emotional responses to being accepted or rejected by peers of different age groups (i.e., early or middle adolescence) and genders. We also tested whether expectations about peers' interest was associated with variability in adolescents' emotional responses to the evaluative outcome. Upon being accepted by middle adolescent male peers, females in the middle relative to early years of adolescence reported greater well-being, whereas males reported similar levels of well-being regardless of their own age. Following acceptance from middle adolescent female peers, females reported greater well-being than males. Adolescents with high expectations for being liked by peers felt better after being accepted versus rejected relative to those with low expectations. For adolescents with low expectations, acceptance and rejection were associated with similar levels of well-being. Adolescents' emotional responses to peer evaluation are influenced by specific individual characteristics and antecedent preparation for evaluation that may serve an emotion regulatory purpose.